Economic Catch-Up between Southern and Eastern Mediterranean Countries and Emerging Asian Economies: The Role of Human Capital - Mazzaourou, Abdeljalil (Technium Social Sciences Journal, 2025)
This article examines the dynamics of economic convergence between the Southern and Eastern Mediterranean Countries (SEMCs) and the Emerging Asian Economies (EAEs) over the period 2000–2022, with a specific focus on the role of human capital. Using an econometric approach based on the conditional convergence model and panel data, the results reveal the existence of a catch-up process reinforced by investment in human capital. Human capital, measured through a composite index of education and health developed using the Principal Component Analysis (PCA) method, stimulates economic growth and accelerates the reduction of development gaps. These findings highlight the strategic importance of education and health policies in promoting rapid and sustainable catch-up among developing countries. The study also opens avenues for integrating institutional and structural variables in future analyses of economic convergence.